The Effect of Using Photographic Image on Students’ Writing Ability at Secondary School - Surniakhrat, Shoumi; Nuardi, Nuardi (Journal of English and Arabic Language Teaching, 2024)
The objectives of the research were to investigate the students’ writing ability in descriptive text taught without using Photographic Image, to investigate the students’ writing ability in descriptive text taught by using Photographic Image and to investigate whether there is a significance difference on students writing ability in descriptive text taught by using Photographic Image to compared the students in the conrol group. In this research, the researcher design was an quasi-experimental research. The populatiom of the research was the eighth grade students of SMP Negeri 4 Koto Gasib in academic year 2021/2022. The total number of population was 38 students. The sample researcher taken from two classes (VIII 1 20 students and VIII 2 18 students). In this research, the researcher used pre-test and post-test to collect the data to find out the students’ writing ability in descriptive text. The technique of analyzing data was an independent sampe T-test through SPSS version 23. The researcher found that Sig. (2 tailed) was 0.001 less than 0.05. it means that Ha is accepted and Ho is rejected. In other words, there is a significant difference in students’ writing ability in descriptive text between taught without and by using Photographic Image at the eighth grade students of SMP Negeri 4 Koto Gasib.